2021
DOI: 10.1186/s12944-021-01462-4
|View full text |Cite
|
Sign up to set email alerts
|

Compared with the monocyte to high-density lipoprotein ratio (MHR) and the neutrophil to lymphocyte ratio (NLR), the neutrophil to high-density lipoprotein ratio (NHR) is more valuable for assessing the inflammatory process in Parkinson’s disease

Abstract: Background The inflammatory response plays essential roles in the pathological process and prognosis of Parkinson’s disease (PD). This research investigated the predictive value of the neutrophil to high-density lipoprotein ratio (NHR), neutrophil to lymphocyte ratio (NLR), and monocyte to high-density lipoprotein ratio (MHR) for PD. Methods Patients with PD (n = 98) were divided into three groups according to disease duration: < 6 years (n = 55… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 47 publications
(28 reference statements)
0
31
1
Order By: Relevance
“…Furthermore, studies have found that high-density lipoprotein (HDL) showed antithrombotic, anti-inflammatory, and antioxidant effects, and HDL can inhibit the oxidation of low-density lipoprotein (LDL) and prevent its negative effects on the endothelium (25). In view of the role of neutrophils, monocytes, lymphocytes, platelets, and HDL in inflammation, the neutrophil/HDL ratio (NHR), lymphocyte/HDL ratio (LHR), monocyte/HDL ratio (MHR), and platelet/HDL ratio (PHR) have been recently investigated as new markers for inflammation, and they were suggested as potential markers of systemic inflammation and oxidative stress in many inflammatory diseases (26)(27)(28)(29)(30). They were found to be closely associated with the presence and prognosis of some physical health disorders, including cardiovascular disease, cancer, Parkinson's disease, ischemic stroke, and erectile dysfunction (24,27,28,31,32).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, studies have found that high-density lipoprotein (HDL) showed antithrombotic, anti-inflammatory, and antioxidant effects, and HDL can inhibit the oxidation of low-density lipoprotein (LDL) and prevent its negative effects on the endothelium (25). In view of the role of neutrophils, monocytes, lymphocytes, platelets, and HDL in inflammation, the neutrophil/HDL ratio (NHR), lymphocyte/HDL ratio (LHR), monocyte/HDL ratio (MHR), and platelet/HDL ratio (PHR) have been recently investigated as new markers for inflammation, and they were suggested as potential markers of systemic inflammation and oxidative stress in many inflammatory diseases (26)(27)(28)(29)(30). They were found to be closely associated with the presence and prognosis of some physical health disorders, including cardiovascular disease, cancer, Parkinson's disease, ischemic stroke, and erectile dysfunction (24,27,28,31,32).…”
Section: Introductionmentioning
confidence: 99%
“…In view of the role of neutrophils, monocytes, lymphocytes, platelets, and HDL in inflammation, the neutrophil/HDL ratio (NHR), lymphocyte/HDL ratio (LHR), monocyte/HDL ratio (MHR), and platelet/HDL ratio (PHR) have been recently investigated as new markers for inflammation, and they were suggested as potential markers of systemic inflammation and oxidative stress in many inflammatory diseases (26)(27)(28)(29)(30). They were found to be closely associated with the presence and prognosis of some physical health disorders, including cardiovascular disease, cancer, Parkinson's disease, ischemic stroke, and erectile dysfunction (24,27,28,31,32). At present, there are few studies on these ratios in psychiatric diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Our research showed that after 12 weeks of HIIT the level of three cellular immune inflammation markers decreased in the PD-TR group, while in the control group, the decrease in the neutrophil/monocyte ratio and increase in the monocyte/ lymphocyte ratio were observed. The neutrophil/lymphocyte ratio is considered a good marker of inflammation and was previously described as elevated in PD patients [34][35][36][37]. In the context of physical exercise, its level was reported elevated after the exercise and decreased after the long-term training events [38].…”
Section: Cellular Immune Inflammation Markersmentioning
confidence: 99%
“…Compared with single monocytes and HDL levels, combining monocytes and HDL to form a new comprehensive inflammatory index that incorporates both the injury mechanism and protection mechanism, namely the MHR, may have greater clinical value as this biomarker can reflect the degree of inflammation and oxidative stress. Many studies have shown that MHR is closely related to Parkinson's disease ( 53 ), ischemic stroke ( 54 ), cardiovascular disease ( 23 ), metabolic syndrome ( 55 ), immune system disease ( 26 ), and rheumatic disease ( 27 ). Related studies have also reported that the neutrophil-to-lymphocyte ratio (NLR) was related to disease activity at the onset of MS ( 56 ).…”
Section: Discussionmentioning
confidence: 99%